Is Indonesia Ready to Serve? : An Analysis of Indonesia’s Primary Health Care Supply-Side Readiness - World Bank Group (World Bank, Washington, DC, 2018)
Health financing in Indonesia is marked by low public health expenditures (PHE), high out-of-pocket (OOP) expenditures and a complex and fragmented intergovernmental fiscal transfer system. Indonesia has a mixed model of public-private provision of health care services. Despite this large network of primary health care facilities, health service delivery is challenging. This report brings out key findings from a Quantitative Service Delivery Study (2016) of public and private primary health care providers in Indonesia. The report analyzes primary health care supply-side readiness across public and private facilities, rural and urban facilities, private facilities empaneled by the national social health insurance agency (Badan Penyelenggara Jaminan Sosial – BPJS) versus those who have not, amongst others. It also compares temporal changes in public-sector primary health care supply-side readiness since the last facility census, the Rifaskes (2011). The primary aim of the report is to present findings from the survey that can inform policy choices to improve primary health care service readiness as part of Indonesia’s path towards achieving Universal Health Coverage (UHC).